ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Ramanisa, Hartiwi; Khairudin, Khairudin; Netti, Syukma (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2020)
The ability Mathematical representation is very important for students to have, because it can facilitate students in solving mathematical problems. This study aims to describe the ability of mathematical representation of class VII students of SMP Negeri 14 Padang. The results showed that 82.7% of students used visual representations, 38% of students used representations of Equation or mathematical expressions and 23.3% of students used representations of words or written texts. The highest indicator of visual representation is to draw geometric figures to clarify the problem and facilitate its solution, while the lowest indicator of the representation of words or written text is to write the steps to solve mathematical problems with words